Tingkat Keamanan Nasi Campur Yang Dijual Di Lingkungan Pasar Badung Ditinjau Dari Aspek Mikrobiologi - Yulianus Jordi Ziku; Ni Made Ayu Suardani Singapurwa; I Wayan Sudiarta (GEMA AGRO, 2018)
Food is one of the main elements of man. Quality of food should always be guaranteed to the public avoid the disease or health problems caused by bacterial contamination. One indicator of food contamination is the bacteria Escherichia coli. This study aims to analyze the contaminants of Escherichia coli bacteria and the total amount of microbes found in mixed rice foods sold in the Badung Market Traditional. This research uses descriptive analysis method. Samples tested were mixed rice taken from six mixed rice vendors in Badung Market environment, and testing of bacterial contaminants was tested at Veterinary Balai Besar Laboratory in Denpasar. The study was conducted on April 7, 2016, until May 4, 2016. The study included E.coli MPN testing, prediction test, confirmatory test, biochemical test using IMViC, and total microbial analysis using Total Plate Count (TPC) testing. The results of this study showed that all samples of mixed rice food (100%) were not contaminated with Escherichia coli bacteria. The total microbial yields showed 91.7% of mixed rice samples did not meet the standards and only 8.3% of the samples met the standards determined by Dirjen POM Number: 03726 B/ SK /VII /89.